The association of eye movements and performance accuracy in a novel sight-reading task - Lucas Lörch (Bern Open Publishing, 2021)
The present study investigated how eye movements were associated with performance accuracy during sight-reading. Participants performed a complex span task in which sequences of single quarter note symbols that either enabled chunking or did not enable chunking were presented for subsequent serial recall. In between the presentation of each note, participants sight-read a notated melody on an electric piano in the tempo of 70 bpm. All melodies were unique but contained four types of note pairs: eighth-eighth, eighth-quarter, quarter-eighth, quarter-quarter. Analyses revealed that reading with fewer fixations was associated with a more accurate note onset. Fewer fixations might be advantageous for sight-reading as fewer saccades have to be planned and less information has to be integrated. Moreover, the quarter-quarter note pair was read with a larger number of fixations and the eighth-quarter note pair was read with a longer gaze duration. This suggests that when rhythm is processed, additional beats might trigger re-fixations and unconventional rhythmical patterns might trigger longer gazes. Neither recall accuracy nor chunking processes were found to explain additional variance in the eye movement data.